SDRE based optimal finite-time tracking control of a multi-motor driving system. Issue 9 (2nd September 2021) - Wang, Minlin; Dong, Xueming; Ren, Xuemei; Chen, Qiang
Abstract : This paper presents a nonlinear optimal finite-time tracking controller based on a state-dependent Riccati equation (SDRE) for the multi-motor driving system (MDS). Conventional fast terminal sliding mode controller (FTSMC) can get the finite-time convergence of the tracking error, but how to achieve the optimality simultaneously is not an easy task. To address this optimal control problem, a SDRE based optimal controller is developed via a fast terminal sliding surface to design the nonlinear optimal feedback of the FTSMC. To further increase the robustness of the SDRE based method, an extended state observer (ESO) and a robust controller are incorporated into the optimal controller design to deal with the system uncertainties and external disturbances. Consequently, the proposed controller can not only guarantee the finite-time stability of the tracking error, but also achieve the optimal control performance under the system unknown dynamics. Experimental results demonstrate the effectiveness of the proposed scheme.